(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the development of sociolinguistic competence in English as a Foreign Language (EFL) classrooms, emphasizing the necessity of teaching language within authentic social contexts. Sociolinguistic competence—an essential component of communicative competence—enables learners to interpret and produce language that is socially and culturally appropriate. The paper outlines practical strategies for EFL instructors to incorporate sociolinguistic principles into language instruction, such as role-plays, discourse analysis, culture-rich materials, and contextualized grammar teaching. Drawing on theoretical models and classroom-based research, this study highlights the importance of context in language acquisition and offers guidance on fostering learners’ abilities to navigate different social registers, speech acts, and cultural nuances effectively.